2024
DOI: 10.1098/rsfs.2023.0082
|View full text |Cite
|
Sign up to set email alerts
|

Wear patterns of radular teeth in Loligo vulgaris (Cephalopoda; Mollusca) are related to their structure and mechanical properties

Svenja Hackethal,
Ellen Schulz-Kornas,
Stanislav N. Gorb
et al.

Abstract: Radular teeth have to cope with wear, when interacting with ingesta. In some molluscan taxa, wear-coping mechanisms, related to the incorporation of high contents of iron or silica, have been previously determined. For most species, particularly for those which possess radulae without such incorporations, wear-coping mechanisms are understudied. In the present study, we documented and characterized the wear on radular teeth in the model species Loligo vulgaris (Cephalopoda). By applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…Similarly to insect mouthparts, the radular teeth of the squid Loligo vulgaris have to cope with wear as well. Mechanisms to maintain a high functionality were investigated using various methods, shedding light on the composition and mechanical properties of the teeth [ 14 ]. Here, authors revealed that tooth regions prone to wear exhibited greater hardness and stiffness, while surfaces interacting with ingesta displayed a protective coating rich in silicon, likely mitigating abrasion.…”
mentioning
confidence: 99%
“…Similarly to insect mouthparts, the radular teeth of the squid Loligo vulgaris have to cope with wear as well. Mechanisms to maintain a high functionality were investigated using various methods, shedding light on the composition and mechanical properties of the teeth [ 14 ]. Here, authors revealed that tooth regions prone to wear exhibited greater hardness and stiffness, while surfaces interacting with ingesta displayed a protective coating rich in silicon, likely mitigating abrasion.…”
mentioning
confidence: 99%